Preparation Of Conjugated Thermo-Sensitive Poly (Nipam) For Affinity Precipitation Of Enzyme - Syaubari, Syaubari (2007)

(untitled)
Affinity precipitation is a recent technique for the purification of enzyme. The precipitation is based upon the interaction between a target enzyme and ligand which binds to the enzyme in a specific manner. Primary-effect affinity precipitation, in which precipitation is a direct result of ligand-enzyme binding, has been the focus of this research. The n-isopropylacrylamide (NIPAM) monomer was synthesized using two methods, chemical and irradiation grafted process polymerization. The various amount of mercaptopropionic acid (MPA) to monomer preparation used resulted in hydrophobic modification of carboxylated poly (NIPAM). Both methods did not have big impact on the lower critical solution temperature (LCST) of polymer but resulted in conjugation of ligand indicating significant difference in synthesized process A ligand-enzyme system used in this study was p-aminobenzamidine-trypsin (PABA-trypsin). Initial studies with the PABA-trypsin system succeed to produce precipitation due to complications with the use of p-aminobenzamidine (PABA) as a ligand. An affinity precipitant for ligand-polymer was then successfully synthesized by conjugation of PABA to thermo-sensitive poly (NIPAM). The effect of molecular weight, reaction time, ligand PABA load, pH condition and addition of NHS on conjugated PABA-poly (NIPAM) were examined including the amount of ligand conjugated and dried weight precipitate of polymer. Trypsin as single enzyme was replaced by enzyme mixture of trypsin and chymotrypsin to evaluate the effect of the specific interaction ligand-enzyme during affinity precipitation. Both methods of preparation polymer chemical and irradiation grafted process successfully were used in the evaluation the reversibility of the precipitation and recovery of the selected enzyme after precipitation. PABA conjugated with thermo-sensitive poly (NIPAM) was used in the affinity precipitation of trypsin. Polymer and ligand concentrations used in conjugate preparation showed remarkable effect on the trypsin recovery. Trypsin precipitation efficiency amounted to 97% and recovery was 81% using prepared polymer by chemical process, and synthesized conjugated poly (NIPAM polymers by irradiation grafted process show the trypsin precipitation efficiency amounted to 95% and recovery was 83%.